CREATIVITY INNOVATION OF MOTIVATIONAL T-SHIRTS AT “M T-SHIRT” SURABAYA - Giri Pamungkas; Cahaya Adinda Putri Ayu; Lidya Putri Nanda; M. Afif Sholehuddin; Yuli Kurniawati (LPPM Universitas Bina Bangsa, 2022)
This study aims to describe the creativity designed for the invention of motivational t-shirts at